E-cigarette devices used on school grounds. (November 2020) - Jackson, Asti; Kong, Grace; Wu, Ran; Morean, Meghan E.; Davis, Danielle R.; Camenga, Deepa R.; Cavallo, Dana A.; Bold, Krysten W.; Simon, Patricia; Krishnan-Sarin, Suchitra
Highlights: E-cigarette use frequency for each device category predicts use of respective devices in school. Current JUUL users frequently reported e-cigarette use in school. Mod e-cigarette use was less frequently reported in school. The bathroom was the most frequently reported place for use of all devices. Adolescents also reported using e e-cigarettes in less discreet places like classrooms. Abstract: Introduction: Preliminary evidence suggests adolescents use e-cigarettes in school. However, little is known about the types of devices that are used in schools, where they are used, and who uses them. Knowledge about these issues is critical to inform school regulations. Methods: Cross-sectional surveys were conducted in 6 Connecticut high schools in 2019. Adolescents reported on current use (past 30-day use) of the following e-cigarette devices inschool: JUUL, any pod system other than JUUL, vape pens, disposables, mods, and on deviceuse in different locations: class, bathroom, hallways, outside on school grounds, and other school locations. Separate binary logistic regressions investigated predictors of use (demographics and past month use frequency of each device) in school for each device. Results: Overall, 45.0% of current users (N = 1447) used e-cigarettes at school. Among users of each device, prevalence of current use at school varied by device with 45.7% reporting JUUL use, 41.3% other pod use, 34.6% vape pen use, 38.3% disposables use and 27.3% mod use. Current users used devices in bathrooms (75.1%), followed by outside on school grounds (52.2%), classrooms (45.7%), hallways (38.8%) and other school locations (11.7%). Greater e-cigarette past month use frequency for each device was associated with device use in school. Conclusions: This study is the first to examine use of specific e-cigarette devices in schools and demonstrates that e-cigarette use frequency predicts school use. Despite rules against vaping, e-cigarette use remains prevalent in many school locations, suggesting alternative strategies such as prevention and e-cigarette education are needed.